The Oil Monopoly in the Arab World - Fawas Habisya (GoAcademica Research & Publishing, 2023)
The Arab world, a region steeped in history and culture, has been inexorably linked with the global oil industry for over a century. Its extensive oil reserves have not only catapulted the region into the international limelight but have also defined the socio-economic, political, and geopolitical landscape of the Middle East and North Africa (MENA). This article embarks on a comprehensive exploration of the historical roots, contemporary status, and multifaceted implications of oil monopolies in the Arab world, transcending mere economics to encapsulate the intricate tapestry of regional dynamics. As a geographical crossroads between Africa, Asia, and Europe, the Arab world's historical importance cannot be overstated. The region has been the cradle of civilization, the birthplace of major religions, and a pivotal hub for trade and knowledge exchange for centuries. However, it wasn't until the early 20th century that the Arab world underwent a transformation that would irrevocably alter its destiny: the discovery of oil.